The Identification of Visitor Activities at Nostalgia Park, Kupang - Neonufa, Suliha Ningsih Imelda; Tualaka, Theodora Murni C.; Hendrik, Maria L. (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
Nostalgia Park, the first planned public open space in Kupang, was designed to serve as a representative recreational area for the city's residents. Since its inauguration in 2011, it has become a focal point for recreational activities within Kupang. Since the space has been open for 13 years, it is essential to define visitor activities before determining the necessary facilities. To develop a comprehensive understanding of the facility requirements necessary to improve the quality of Nostalgia Park as a public space, this research examined fundamental inquiries regarding existing visitor activities. The study used behavioural mapping with a place-centered approach, observing specific zones and periods to identify user activity locations and types. The findings of the survey were subjected to descriptive analysis to inform the formulation of facilities. The research, conducted over two weeks, yielded an overview of the condition of the Nostalgia Park. The highest density of activity was observed in zone B, while zone A exhibited the lowest activity. The majority of visitors are present on weekends and holidays, with the highest concentration of activity occurring in the afternoon, between 15:00-17:00 WITA. Based on these findings, the necessary facilities for each zone have been identified, with their distribution adjusted to accommodate the activity levels.